Application of wastewater for reclamation of desert: A life cycle cost analysis - Pandey, Rajan Raj; Al-Odaini, Aiman Abdullah; Giri, Om Prakash (International Journal of Innovative Research and Scientific Studies, 2025)
This article explores the financial potential of using wastewater for desert reclamation to convert barren land into arable areas capable of growing food in hunger-affected regions. It emphasizes the need to assess the financial feasibility of such projects, providing a detailed Life Cycle Cost calculation to evaluate the long-term financial viability before initiating pilot experiments. The article compares the Net Present Value (NPV) of agro products and the system after 15 years against the NPV of Life Cycle Costs incurred. It reveals a 15-year deficit of USD 292,312 per hectare in desert reclamation through continuous wastewater application over three years in each plot, and this is the first kind of work that combines LCCA with wastewater application and desert reclamation. Reclaimed desert land can be used to produce grains, oilseeds, and cotton indefinitely, providing long-term agricultural benefits. Additionally, the increased greenery plays a crucial role in carbon sequestration. This transformation not only boosts food production but also enhances environmental quality by reducing carbon dioxide levels and improving local ecosystems, making desert reclamation a sustainable solution for both food security and environmental preservation.